Physical demands in elite team handball: Comparison between male and female players - Michalsik, L. B.; Aagaard, P.; Madsen, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: In elite Team Handball, the physical capacity of the players has a crucial influence on playing performance. The central areas of physical training seem in general to be the same for male and female players, however physical demands may yet vary among the sexes. Therefore, the present study examined possible differences in physical demands between male and female elite TH players, which were closely monitored over a six and five season time span, respectively. Methods: Each player was evaluated during match-play using video recording and subsequent computerized locomotive and technical match analysis. Further, physiological measurements during match-play, physical testing and anthropometric measurements were also carried out. Results: Women (n=83) performed a longer mean total distance covered (TDC) per match (4002±551 m) (group means±SD) compared to men (n=83) (3627±568 m, p<0.05) despite less mean total effective playing time (TPT) (50.70±5.83 min vs. 53.85±5.87 min). Women spent substantial less time standing still (10.8±3.8 % of TPT per match) compared to men (36.9±8.6 %, p<0.001) and worked with a greater mean relative physical load (RWL, 79.4±6.4 % of VO2-max) than men (70.9±6.0 % of VO2-max, p<0.05). Women performed less amount of high-intensity running per match (2.6±1.8 % of TDC) compared to men (7.9±4.9 %, p<0.01) and also had markedly fewer number of activity changes (663.6±100.1) than men (1482.4±312.6, p<0.001). Men performed a higher number of high-intense playing actions per match (36.9±13.1) than women (28.3±11.0, p<0.05). In offence, men received more tackles (34.5±11.2) and gave more tackles (29.9±8.2) while in defence compared to women (14.6±5.7, 20.7±6.1, p<0.05). Mean body height and body mass in the Danish Premier Team Handball League was significantly higher for men (189.6±5.8 cm, 91.7±7.5 kg) compared to women (175.4±6.1 cm, 69.5±6.5 kg, p<0.001). Identical positional differences in the physical demands were demonstrated irrespectively of gender, with wing players performing more high-intensity running and less physical confrontations than backcourt players and pivots (p<0.01). Conclusions: In conclusion, substantial gender-specific differences in the physical demands were observed, where male elite TH players performed more high intense, strength-related actions and more high-intensity running than female elite TH players. Conversely, female players covered a greater total distance and worked with a higher RWL than their male counterparts. Consequently, female players should therefore focus relative more on aerobic training and relative less on anaerobic training and strength training. In both genders, wing players performed more high-intensity running and less physical confrontations than all other players. The planning of the physical training in both sexes should be directed at the specific playing position and the players´ individual physical capacity.